الوضع الحالي والمستقبلي للنقل الجوي في مصر - محمد، أشرف عبدالوهاب راتب (المعهد العالي للدراسات النوعية, 2023)
تحتاج مصر إلى المزيد من الاستثمارات السياحية وخاصة في مجال النقل الجوي من أجل تحفيز النمو الاقتصادي، وخلق مزيد من فرص العمل المباشر وغير المباشر في قطاع السياحة، وتقليص مشكلتي الفقر والبطالة، بالإضافة إلى الحاجة الماسة للأساليب الإدارية والتكنولوجية الحديثة، وتتمثل مشكلة الدراسة في تذبذب حجم الاستثمارات في النقل الجوي من عام إلى آخر وضآلتها، وبالتالي ضرورة البحث عن الآليات والسبل اللازمة لتشجيع وتنشيط الاستثمارات بها في مصر، والوقوف على الأسباب الحقيقية وراء تذبذب هذه الاستثمارات وضآلتها، باعتبار أن الاستثمارات بصفة عامة هي أساس النمو والتنمية الاقتصادية، لما لها من أثار إيجابية على أداء الاقتصاد المصري، فقد سعت مصر خلال المراحل الاقتصادية المختلفة إلى تنشيط الاستثمار، وذلك بانتهاج سياسات للإصلاح الاقتصادي، وإصدار العديد من التشريعات والقوانين لتهيئة المناخ الاستثماري، وعلى الرغم من إدخال العديد من التعديلات على القوانين والتشريعات في مصر بهدف تشجيع وجذب الاستثمارات المحلية والأجنبية وخاصة المباشرة منها، فإنها لم تنجح في أن تصبح موقع جذب للاستثمارات السياحية وخاصة في مجال النقل الجوي، ومما سبق يمكن تلخيص مشكلة الدراسة في سؤالين هما، ما هو الوضع الراهن للاستثمار في النقل الجوي في مصر من ناحية، وما هي أهم معوقات النقل الجوي في مصر من ناحية أخرى، ويهدف البحث إلى تقديم صورة عامة عن موقف أداء النقل الجوي في مصر من ناحية مدى الاستغلال الاقتصادي للإمكانيات المتاحة والوضع التنافسي للقطاع، هذا بالإضافة إلى دراسة التحديات التي تواجه قطاع النقل الجوي في مصر، واعتمدت الدراسة في تحقيق أهدافها وفروضها المنهج الاستقرائي في التوصل لنتائجها إذ يتم الاعتماد على تحليل وأداء شركات النقل الجوي وتطور حجم حركة النقل وتوزيعها على المطارات وذلك للحكم على موقف أداء قطاع النقل الجوي في مصر ككل، كذلك تم الاعتماد أيضا على المنهج التاريخي المقارن والتحليل الإحصائي لتحليل مجموعة من السلاسل الزمنية التاريخية لحجم النقل الجوي في مصر للوصول إلى حكم عام عن كفاءة قطاع النقل الجوي في مصر. Egypt needs more tourism investments, especially in the field of air transport, in order to stimulate economic growth, create more direct and indirect job opportunities in the tourism sector, and reduce the problems of poverty and unemployment, in addition to the urgent need for modern administrative and technological methods. Investments in air transport from year to year and their meagerness, and consequently the need to search for mechanisms and ways to encourage and revitalize investments in them in Egypt, and to find out the real reasons behind the fluctuation and meagerness of these investments, given that investments in general are the basis of growth and economic development, because of their positive effects. On the performance of the Egyptian economy, during the various economic stages, Egypt sought to stimulate investment, by adopting economic reform policies, and issuing many legislations and laws to create the investment climate, despite the introduction of many amendments to laws and legislations in Egypt with the aim of encouraging and attracting local and foreign investments, especially It has not succeeded in becoming an attractive site for tourism investments, especially in the field of air transport From the above, the problem of the study can be summarized in two questions: What is the current situation of investment in air transport in Egypt on the one hand, and what are the most important obstacles to air transport in Egypt on the other hand, and the research aims to provide a general picture of the position of air transport performance in Egypt from In terms of the extent of the economic exploitation of the available capabilities and the competitive situation of the sector, in addition to studying the challenges facing the air transport sector in Egypt. In order to judge the position of the performance of the air transport sector in Egypt as a whole, it was also relied on the comparative historical method and statistical analysis to analyze a group of historical time series of the volume of air transport in Egypt to reach a general judgment about the efficiency of the air transport sector in Egypt. In light of the above, the study recommends: 1- Paying attention to the development of existing airports and providing the necessary infrastructure to face the influx of incoming tourist delegations, especially in light of GATT decisions regarding opening the skies. 2- Accelerating the easing of administrative restrictions such as financing the purchase of new aircraft and projects for developing corridors by offering shares to citizens, whether Egyptians or foreigners, similar to the partial privatization system or bonds, provided that the holder is given special privileges such as a discount on company tickets, reservation priority, or participation in a travel program that allows free flights. With a certain number of kilometers traveled 0 3- Attempting to find a kind of coordination and joint cooperation between the national partnership and the private companies operating in the field of air transport in Egypt in a way that does not create competition among them. 4- Attempting to increase demand rates for airlines operating in the Egyptian market by establishing a multimodal transport company that provides its services to different companies and between different means of transport, provided that it provides its services at the lowest possible expense, allowing it to compete in the global market 5- Serious work to establish an Arab and regional bloc governed by common economic interests, whether at the national or corporate level on the one hand, and revitalizing cooperation between African national companies in preparation for the establishment of a strong African alliance in the field of air transport on the other hand
Keywords: النقل الجوي -- الإستثمارات السياحية -- التنمية الإقتصادية -- مصر